Clinical practice guideline for clozapine use in patients with COVID‐19. Issue 1 (9th February 2023) - Ansari, Saba; Kelbrick, Marlene; Paduret, Gabriela; Diaz, Natasha; Menzel, Rose; Rogers, Rowena; Wareham, Claire; Griffiths, Chris; Jugon, Sue; Tidy, Katy; Johnson, Sara; Mann, Nick; et al.
Abstract : National and local guidelines focus mainly on clozapine monitoring frequency, and actions based on full blood count results. Prescribing clozapine in the context of COVID‐19‐positive patients brings a complexity of challenge beyond this. In this article the authors put forward an example of a practical clinical guideline in this regard.